CORAL REEF HEALTH ASSESSMENT ON THE EAST COAST OF KEI BESAR ISLAND, SOUTHEAST MALUKU - Dea Fauzia Lestari; Astri Ayuningtias; Endang Sunarwati Srimariana (Jurnal Teknologi Perikanan dan Kelautan)
Kei Besar Island in Southeast Maluku has significant ecological coral reef potential, making it a regionally important area with great development opportunities. Like other coastal coral ecosystems, the reefs around Kei Besar Island are highly vulnerable to substantial threats from human activities and environmental pressures. A crucial initial step is to understand the ecosystem's condition through a coral reef health analysis. The purpose of this study was to analyze the reef health index in the coastal waters east of Kei Besar Island. Field data were collected from November 3-18, 2018, across six locations on the east coast of Kei Besar Island. These specific locations were chosen due to their dense populations along the eastern coast. The findings showed that coral reef ecosystems in eastern Kei Besar generally fall into the moderate to high health categories. Hard coral cover ranged from a low of 27% in Hollat to a high of 78.67% in Fako. Target fish biomass varied from 32.92 kg/ha in Kilwait (the lowest) to 311.41 kg/ha in Weduar (the highest). The coral reef health index on the east coast of Kei Beasr Island generally has a score of 6 out of a total of 10, and only Hollat has a score of 5.